A model with interacting composites - Hortacsu, M.; Lutfuoglu, BC (World Scientific Pub Co Pte Lt, 2006)
We show that it is possible to construct a model in (3 + 1) dimensions where only composite scalars take place in physical processes as incoming and outgoing particles, whereas constituent spinors only act as intermediary particles. Hence while the spinor–spinor scattering goes to zero, the scattering of composites give nontrivial results.
Keywords: High Energy Physics - Theory; High Energy Physics - Theory (hep-th); FOS: Physical sciences